Sifat Dua Puluh Telaah Pemikiran Al – Fudholi dalam Kitab Kifayatul Awwam - Ibnu Alwi Jarkasih Hrp; Radhinal Abdullah; Sapri Sapri (Transformasi Manageria: Journal of Islamic Education Management, 2024)
The book Kifayatul Awwam, an important work in Islamic literature, was written by Al-Fudholi, a famous Muslim scholar. This book is famous for presenting broad Islamic teachings, especially the attributes of Allah. This research uses the Library Research method by utilizing data and literature in this writing. The research aims to provide a general understanding of the twenty characteristics contained in the book kifayatul awwam. The book kifayatul awwam includes twenty characteristics that are very important to understand in Islamic teachings, because they are the basis of the Islamic faith. Some of the characteristics discussed in this book include the characteristics of obligatory, impossible and jaiz for Allah. The twenty characteristics contained in the book kifayatul awwam have an important role in forming the creed of the Islamic ummah. Understanding and implementing this characteristic is an important part of the spiritual journey of a servant's life.